Implementasi Kurikulum Pembelajaran Aksara Arab Melayu Kelas IV dI SD Al-Azhar Medan Sumatera Utara - Mursal Aziz; Arwita Putri; Azimah Azzahra; Ririn Indriani (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
Learning Malay Arabic script is part of the school curriculum, learning Arabic Malay is included in the category of local content learning. It cannot be guaranteed that all schools or madrasas have a Malay Arabic script curriculum, there are also some schools that do not use the Malay Arabic script as local content. In this research, researchers conducted research at SD Al Azhar Medan regarding the analysis of the implementation of the Arabic Malay Script learning curriculum at SD Al Azhar Medan including methods, strategies, evaluation tools, and difficulties felt by teachers in teaching Arabic Malay Script learning. This research uses a qualitative research approach with descriptive methods. Data collection techniques use observation, interviews and documentation methods. The aim of teaching Malay Arabic Script in schools is to develop students' language skills in mastering reading and writing Malay Arabic Script. Malay Arabic script is an important lesson in the curriculum as a local content curriculum so that the Malay Arabic script must be designed as well as possible during learning, in order to create an active and creative learning atmosphere.